2010
DOI: 10.1097/meg.0b013e32832b9c53
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in dietary coping with gastrointestinal symptoms

Abstract: Aim Nutritional changes are often considered first line treatment in public health diseases which apply to many gastrointestinal disorders, since different food and beverages may modulate gastrointestinal (GI) motor and sensory functions, and provoke GI symptoms. The aim of this study was to examine dietary coping and possible changes of food and beverages intakes in relation to GI symptoms reported by identified IBS patients compared to healthy controls and if any gender differences were seen in these respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…In addition, women in the CSM group had greater change scores in self-reported stress levels than those in the UC group. In another study, women with IBS were more likely to change dietary habits following a dietary intervention as compared to men (Faresjo, Johansson, Faresjo, Roos, & Hallert, 2010). In IBS, male versus female differences may be due to differences in coping style, higher levels of somatic and psychological symptoms, and health seeking patterns (Hungin, Chang, Locke, Dennis, & Barghout, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women in the CSM group had greater change scores in self-reported stress levels than those in the UC group. In another study, women with IBS were more likely to change dietary habits following a dietary intervention as compared to men (Faresjo, Johansson, Faresjo, Roos, & Hallert, 2010). In IBS, male versus female differences may be due to differences in coping style, higher levels of somatic and psychological symptoms, and health seeking patterns (Hungin, Chang, Locke, Dennis, & Barghout, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of caffeine in IBS is less clear[17]. Several studies have indicated coffee and tea among the foods associated with symptoms by IBS patients[8,10,25]. On the other hand, habits of coffee drinking have not been noted to be more common among IBS patients than among healthy controls[18,19].…”
Section: First-line Dietary Approach In Ibsmentioning
confidence: 99%
“…An important proportion of patients with IBS relate symptoms to foods rich in fat[8,25,26]. As a consequence, the avoidance of fatty foods is one of the most frequent dietary approaches considered by IBS patients for symptoms improvement[36].…”
Section: First-line Dietary Approach In Ibsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 A substantial number of people with IBS report that their symptoms are associated with fatty food, and that they frequently avoid fatty foods to alleviate the symptoms. 19,21,39,40 In people with IBS, the lipid-induced inhibition of gut-propulsive motility is up-regulated, and the colonic hypersensitivity in response to the duodenal lipid infusion is exacerbated. 39,41,42 These effects may be associated with various IBS symptoms.…”
Section: Diet and Intestinal Microbiotamentioning
confidence: 99%